(untitled) (World Science, 2022)
Combustible ethanol was obtained from agricultural waste. Test samplesE0 (petrolgazoline) and E5, E10 and E20 (epanpl/gazoline blend) were prepared and their physical, chemical and technical characteristics were studied. The effect of bioethanol on the ecological compatibility of the automobile engine has been studied. The objects of research were Regular, Premium and Super of Petrol gasoline Samples, as well as a of 10%, 20% and 30%. bioethanol/gazoline blends. The study of the ecological properties of the test additive was carried out at the stand of automobile engines SAK-670 (Germany), on which the engine of a BMW-316 car with coupling sleeve and a transmission assembly is installed. The stand is equipped with brakes and torque sensors, as well as with crankshaft speed and fuel consumption measuring instruments. The test mixtures during an idle running of engine cause a decrease in the CO content in the exhaust gases by 10-16%, and this taking into account their low cost, indicate the prospect of expanding the use of fuel ethanol.